Ruined Platform to the south of Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
A ruined platform stands south of the main Bhandasar Temple, in front of the Adinatha Temple. The south-facing side of the platform has a staircase. The purpose of this platform is not known.